2023
DOI: 10.1055/a-2036-0510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Multifrequency Narrow-Band CE-Chirp and Tone Burst Evoked Cervical Vestibular Evoked Myogenic Potentials

Abstract: Background: Cervical Vestibular Evoked Myogenic Potentials (cVEMPs) are inhibitory myogenic responses that have commonly been elicited using a variety of stimuli. Yet, the comparison of the effects of multi-frequency tone bursts and narrowband Claus Elberling chirps (NB CE-chirps) on cVEMPs has never been studied in homogeneous age groups. Purpose: The present study focused on comparing the effect of multi-frequency NB CE-chirps and tone bursts on the various parameters of cVEMP responses in normal-hearing you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In particular, relative to the 500 Hz tone burst, several studies found the P1–N1 amplitude to be larger for the chirp stimulus 18 , 20 , 22 , 23 . On the contrary, in other studies, the P1–N1 amplitude was found to be comparable between the two stimuli 24 26 , as well as lower for the chirp stimulus 17 . Owing to the conflicting findings in the literature, the aim of this meta-analysis is to provide more plausible evidence as to whether the NB CE-Chirp stimulus is superior to the conventional 500 Hz tone burst in the cVEMP testing.…”
Section: Introductioncontrasting
confidence: 58%
See 4 more Smart Citations
“…In particular, relative to the 500 Hz tone burst, several studies found the P1–N1 amplitude to be larger for the chirp stimulus 18 , 20 , 22 , 23 . On the contrary, in other studies, the P1–N1 amplitude was found to be comparable between the two stimuli 24 26 , as well as lower for the chirp stimulus 17 . Owing to the conflicting findings in the literature, the aim of this meta-analysis is to provide more plausible evidence as to whether the NB CE-Chirp stimulus is superior to the conventional 500 Hz tone burst in the cVEMP testing.…”
Section: Introductioncontrasting
confidence: 58%
“…Subsequently, two articles were excluded due to ineligible study outcomes. In particular, studies conducted by Mat et al 22 and Neupane and Lodha 26 did not provide the respective mean and standard deviation values of cVEMP parameters. Additionally, an article authored by Moinudeen et al 20 was retrieved using the citation search method (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations